THE ROLE OF THE SERVICE SECTOR IN REDUCING POVERTY: INTERNATIONAL EXPERIENCE AND REGIONAL PERSPECTIVES - Adilbay Dauletmuratov (American Journals, 2025)
The article explores the growing importance of the service sector as a key driver in reducing poverty, especially in developing and transition economies. Based on empirical data and international experience, it highlights how service sector expansion fosters employment, enhances income distribution, and stimulates human capital development. Particular attention is given to the role of education, healthcare, tourism, ICT, and financial services in achieving inclusive growth in Uzbekistan and the Republic of Karakalpakstan. The study also proposes a set of strategic recommendations to strengthen service-oriented economic models for poverty reduction.
Keywords: Service economy, poverty reduction, inclusive growth, employment, human capital, regional development, sustainable development, social inclusion, income inequality, entrepreneurship, digital transformation, public–private partnership (PPP), financial inclusion, education services.